Use of beta-tricalcium phosphate bone graft in dental implants for bone regeneration - Rodríguez, Valentina Rodríguez; Gonzales, Angie Paola Giménez; Avila, Jaime Guzmán; Caballero, Antonio Diaz (Bionorte, 2022)
Objective: to avoid alveolar bone loss and prevent bone resorption and implant failure through the use of beta-tricalcium phosphate bone graft. Case Report: 43-year-old patient who underwent dental extraction of the upper right canine due to root fracture; subsequently, a Bicon® dental implant was placed accompanied by a bone regeneration process in the peri-implant space with beta-tricalcium phosphate substitute and collagen plug, preserving the alveolar bone and papillary gingiva. Results: adequate healing was observed, without gingival retraction. When evaluating the final tomography, an increase in bone tissue was observed at the intervention site with greater measurements than the initial ones and without bone resorption. A fixed temporary crown was made on a temporary abutment which allows the soft tissues to be conditioned, improving the emergence profile for the final crown.